Information and control preferences and their relationship with the knowledge received among european joint arthroplasty patients - Klemetti, Seija; Leino-Kilpi, Helena; Charalambous, Andreas; Copanitsanou, Panagiota P.; Ingadottir, Brynja; Istomina, Natalja; Katajisto, Jouko K.; Unosson, Mitra; Zabalegui-Yárnoz, Adelaida; Valkeapaa, Kirsi (My University, 2016)
Background: The prevalence of joint arthroplasties is increasing internationally, putting increased emphasis on patient education. PURPOSE: This study describes information and control preferences of patients with joint arthroplasty in seven European countries, and explores their relationships with patients' received knowledge. METHODS: The data (n = 1,446) were collected during 2009-2012 with the Krantz Health Opinion Survey and the Received Knowledge of Hospital Patient scale. RESULTS: European patients with joint arthroplasty had low preferences. Older patients had less information preferences than younger patients (p =.0001). In control preferences there were signifi cant relationships with age (p =.021), employment in healthcare/social services (p =.033), chronic illness (p =.002), and country (p =.0001). Received knowledge of the patients did not have any relationships with information preferences. Instead, higher control preferences were associated with less received knowledge. CONCLUSION: The relationship between European joint arthroplasty patients' preferences and the knowledge they have received requires further research.
Keywords: Patients; Health care; Orthopedic surgery patients; Surgical patients